H3K4 acetylation, H3K9 acetylation and H3K27 methylation in breast tumor molecular subtypes. (July 2016) - Judes, Gaëlle; Dagdemir, Aslihan; Karsli-Ceppioglu, Seher; Lebert, André; Echegut, Maureen; Ngollo, Marjolaine; Bignon, Yves-Jean; Penault-Llorca, Frédérique; Bernard-Gallon, Dominique
Aim: Here, we investigated how the St Gallen breast molecular subtypes displayed distinct histone H3 profiles.Patients & methods: 192 breast tumors divided into five St Gallen molecular subtypes (luminal A, luminal B HER2-, luminal B HER2+, HER2+ and basal-like) were evaluated for their histone H3 modifications on gene promoters.Results: ANOVA analysis allowed to identify specific H3 signatures according to three groups of genes: hormonal receptor genes ( ERS1, ERS2, PGR ), genes modifying histones ( EZH2, P300, SRC3 ) and tumor suppressor gene ( BRCA1 ). A similar profile inside high-risk cancers (luminal B [HER2+], HER2+ and basal-like) compared with low-risk cancers including luminal A and luminal B (HER2-) were demonstrated.Conclusion: The H3 modifications might contribute to clarify the differences between breast cancer subtypes.